Enhancing IoT Device Responsiveness with Dual Feedback Schmitt Trigger Optimization - Ramsamuzh, Mourya Anjali; Kannaujiya, Aryan; Lodhi, Pankaj; Srivastava, Vaibhava; Kaur, Amrinder (Proceedings (International Confernce on Computational Intelligence and Communication Networks), 2024)
This brief discusses the operation of a double feedback classical Schmitt trigger with low power consumption for IoT applications. The findings suggest that the PFC-IST exhibits low power consumption with sharp transition. It is highly reliable for fluctuating voltages. The dynamic and leakage power consumption are 1.75× and 1.35×. Further, the propagation delay is 1.30 × times of the conventional circuit. The proposed PFC-IST enhances IoT applications by achieving lower power consumption, faster switching, and improved noise immunity. Unlike conventional Schmitt triggers, the PFC-IST integrates an optimized feedback loop that provides higher stability against input fluctuations, reducing dynamic and leakage power.